EQUILIBRIUM CURRENT VARIANCE IN SEMICONDUCTORS - Ash. V. Surmalyan; R. V. Hovhanisyan; S. V. Melkonyan
The current equilibrium fluctuations appearing in homogeneous and non-degenerate thermal equilibrium semiconductors are considered. As independent sources of equilibrium current fluctuations an electron intraband scattering, generation-recombination transitions and the shot effect are discussed. Variances of electron current equilibrium fluctuations are calculated and analyzed. It is established that not only the electron intraband scattering (Nyquist thermal noise) but also generation-recombination transitions and the shot effect, can be equilibrium noise sources.
Keywords: Physics; Materials science